Nilai Dan Fungsi Tradisi Ziarah Di Dusun Kawangan - Syaifullah, Syaifullah; Safitri, Eqlima Dwiana (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This paper is entitled Values and Functions of the Pilgrimage Tradition in Kawangan Hamlet, precisely in Ngadirejo, Temanggung, Central Java. The aims of this study are: (1) Describing the factors of the perpetuation of the pilgrimage tradition in the village of Kawangan. (2) Knowing the value and function of the pilgrimage tradition in the village of Kawangan in Bronislow Malinowski's theory of functionalism. This study uses a qualitative method, described descriptively. Collecting data has done through field studies: interviews, observations, participant observers and literature studies. The pilgrimage ritual in the village of Kawangan is still sustainable until now because of the local community trust, the loyalty to the ancestral heritage and the integrative needs. While the values and functions of pilgrimage ritual are: (1) Religious Functions, (2) Social Functions, (3) Economic Functions and (4) Entertainment Functions.Tulisan ini berjudul Nilai dan Fungsi Tradisi Ziarah di Dusun Kawangan, tepatnya di Ngadirejo, Temanggung, Jawa Tengah. Tujuan dari penelitian ini yaitu; (1) memaparkan faktor-faktor langgengnya tradisi ziarah di dusun Kawangan; (2) mengetahui nilai dan fungsi tradisi ziarah di dusun Kawangan dalam teori fungsionalisme Bronislow Malinowski. Penelitian ini menggunakan metode kualitatif, dipaparkan secara deskriptif. Pengumpulan data melalui studi lapangan: wawancara, observasi, pengamatan terlibat (participant observer) dan studi pustaka. Ritual ziarah di dusun Kawangan tetap lestari sampai sekarang dikarenakan; kepercayaan masyarakat lokal, kesetiaan memegang teguh warisan leluhur dan kebutuhan integratif. Sementara nilai dan fungsinya adalah, (1) fungsi keagamaan, (2) fungsi sosial, (3) fungsi ekonomi dan (4) fungsi hiburan.